An Appraisal Analysis in the Novel Shine by Jessica Jung - Mega Putra, Rangga; Aini, Nurul; Dwi Agustina, Diyah (CV. Creative Tugu Pena, 2024)
This research investigated to determine the type of Appraisal Attitude contained in a novel by Jessica Jung entitled